Effective Ways to Realise Policy Reforms in Health Systems - Hurst, Jeremy (OECD Health Working Papers, 2010)
Sometimes it is argued that the content of a reform is less important in determining whether or not it receives public and legislative approval than the timing of the proposal; the way in which the reform is presented; the discussions with stakeholders; and a multitude of other factors. The OECD has a crosscutting project on these issues, entitled Making Reform Happen. A number of OECD directorates are considering the factors lying behind successful implementation of reforms in their different policy areas, including tax, environment, agriculture, trade, competition, education, health, pensions, product markets and labour markets